The middle-income trap from a Schumpeterian perspective - Philippe Aghion; Cagatay Bircan (Asian Development Bank (ADB), 2017)
We provide an outline for viewing the middle-income trap through the lens of the Schumpeterian growth paradigm, which places the notion of creative destruction at the center of economic growth. Economic growth and development come from the interplay between changes in economic structure and supporting institutions at different stages of development, i.e., structural transformation. We present a view of the process of economic development that takes the microlevel growth of firms and their competitive interaction as its building blocks. We discuss how institutional factors affect the evolution of these building blocks in understanding growth outcomes at different stages of development.
Keywords: O10; O11; O30; O40; 330; competition; creative destruction; middle-income trap; Schumpeterian growth